Alternative Control of the Leaf-Cutting Ant Atta bisphaerica Forel (Hymenoptera: Formicidae) Via Homeopathic Baits - Vânia Maria Ramos; Fabiane Cunha; Karen Carolina Kuhn; Rafael Gervasoni Ferreira Leite; Wellington Franckievicz Roma (Sociobiology)
Leaf-cutting ants are pests that afflict diverse crops, and are most efficiently controlled by chemical methods that are widely utilized. Other methods have been investigated aiming to efficiently control these insects while reducing the environmental impact of applying such chemical products. Therefore, an assay was conducted to evaluate the efficiency of baits, formulated homeopathically, in nests of the leaf-cutting ant Atta bisphaerica, in the field. Thirty (30) colonies were chosen and divided into 10 repetitions for each of the following treatments: control (without baits), standard (8 g/m2 of loose soil of baits based on sulfluramid 0.3%) and homeopathic (60 g/m2 of loose soil of homeopathic baits parceled into 20g/m2 doses applied on 3 consecutive days). At 24 hours after bait application on active foraging trails of colonies, evaluation of parameters was initiated: loading and return of the baits, foraging and mortality. The completed assay demonstrated that the transport of baits was greater in the standard (80%) than the homeopathic treatment (50%), and, to the contrary, the return of baits was significantly higher in the homeopathic treatment (15%) versus the conventional, where return/rejection did not occur. Colony mortality was 20% under the homeopathic treatment, differing statistically from the 80% value produced by the standard treatment. Thus, the homeopathic treatment is not demonstrated to be efficient at controlling leaf-cutting ants, suggesting new studies with different methodologies.